Use of the MOOC for a Change of Attitude Towards Science and its Teaching - Aoulad Moussa, Rajaa; Madrane, Mourad; Janati-Idrissi, Rachid; Laafou, Mohammed (Transactions on Engineering and Computing Sciences, 2017)
This work describes conceptual changes in science and its teaching; Observed among 200 primary school teachers after the application of a didactic proposal (on-line training). We used a platform as training and learning space to apply the didactic proposal. Attitudes were assessed by means of an instrument, applied before and after the proposal. The instrument included the three traditional components of attitude (cognitive, affective and active) across different scales, semantic differential and forced option reagents. The results of the preliminary survey, carried out before the didactic intervention, revealed that primary school teachers have notions, emotions and actions, which translate into unfavorable attitudes towards natural sciences, which directly affect their teaching practice. After the application of online training, it was obvious both qualitatively and quantitatively a positive change in the attitudes of teachers towards science and its teaching.